2018
DOI: 10.3201/eid2409.180625
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole-Resistant Candida parapsilosis Bloodstream Isolates with Y132F Mutation in ERG11 Gene, South Korea

Abstract: We recently observed the emergence of fluconazole-resistant Candida parapsilosis bloodstream isolates harboring a Y132F substitution in Erg11p in South Korea. These Y132F isolates had a higher propensity to cause clonal transmission than other fluconazole-resistant isolates and persisted within hospitals for several years, as revealed by microsatellite typing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
85
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 7 publications
12
85
1
4
Order By: Relevance
“…Resistance may occur in one of the following ways: (a) point mutations in ERG11 gene, resulting in reduced azole binding affinity; (b) overexpression of the drug target ( ERG11 ) gene which encodes for 14α demethylase; (c) overexpression of the genes encoding multidrug transporters [ATP binding cassettes (ABC) and major facilitator superfamily (MFS)]; (d) overexpression of CDR1 and CDR caused by activating mutations in the transcription factor genes TAC1 leading to efflux of all azole antifungal agents 8 ; (e) overexpression of an MFS transporter ( MDR1 ) caused by activating mutations in the transcription factor genes MRR1 leading to efflux of fluconazole and voriconazole 9‐11 ; and (f) mutations in ERG3 gene resulting in the inactivation of sterol desaturase. A number of studies from the United States of America, United Kingdom, Brazil, Portugal, South Korea and India have recently explored the possible mechanisms of azole resistance in C parapsilosis strains 12‐17 . Souza et al (2015) demonstrated that not only does upregulation of MDR1 and amino acid substitutions in ERG11 lead to resistance to fluconazole but upregulation of ERG11 and CDR1 are involved as well 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Resistance may occur in one of the following ways: (a) point mutations in ERG11 gene, resulting in reduced azole binding affinity; (b) overexpression of the drug target ( ERG11 ) gene which encodes for 14α demethylase; (c) overexpression of the genes encoding multidrug transporters [ATP binding cassettes (ABC) and major facilitator superfamily (MFS)]; (d) overexpression of CDR1 and CDR caused by activating mutations in the transcription factor genes TAC1 leading to efflux of all azole antifungal agents 8 ; (e) overexpression of an MFS transporter ( MDR1 ) caused by activating mutations in the transcription factor genes MRR1 leading to efflux of fluconazole and voriconazole 9‐11 ; and (f) mutations in ERG3 gene resulting in the inactivation of sterol desaturase. A number of studies from the United States of America, United Kingdom, Brazil, Portugal, South Korea and India have recently explored the possible mechanisms of azole resistance in C parapsilosis strains 12‐17 . Souza et al (2015) demonstrated that not only does upregulation of MDR1 and amino acid substitutions in ERG11 lead to resistance to fluconazole but upregulation of ERG11 and CDR1 are involved as well 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Os azólicos são os fármacos mais utilizados para o tratamento de infecções por Candida spp., principalmente o FLC, devido ao seu baixo custo e toxicidade, além de excelente biodisponibilidade em diferentes formulações (Ben-Ami, 2018;De Oliveira Santos et al, 2018). No entanto, são vários os relatos de desenvolvimento de resistência a esta classe de antifúngico, inclusive em C. parapsilosis (Choi et al, 2018;De Oliveira Santos et al, 2018;Maria et al, 2018). A presente investigação microbiológica revelou a emergência de isolados resistentes ao FLC e VRC, em dois hospitais universitários públicos brasileiros.…”
Section: Discussionunclassified
“…A contribuição de mutações presentes no gene ERG11, para a resistência aos azólicos em C. parapsilosis, foi demonstrada em estudos prévios (Berkow et al, 2015;Grossman et al, 2015;Asadzadeh et al, 2017;Choi et al, 2018). Na presente análise, a mutação A395T no gene ERG11, foi identificada exclusivamente entre isolados resistentes ao azólicos do HUMAP-UFMS (Tabela 7).…”
Section: Discussionunclassified
See 2 more Smart Citations